Midterm Outcome After Septal Myectomy and Medical Therapy in Mildly Symptomatic Patients With Hypertrophic Obstructive Cardiomyopathy - Sun, Jiejun; Liang, Lin; Li, Peijin; Jiang, Tengyong; Yu, Xianpeng; Ren, Changwei; Dong, Ran; He, Jiqiang (Frontiers in Cardiovascular Medicine, 2022)
Objective The purpose of this study was mainly to determine the long-term outcome of septal myectomy (SM) and medical therapy in mildly symptomatic patients (NYHA class II) with hypertrophic obstructive cardiomyopathy (HOCM). Methods The study cohort consisted of 184 mildly symptomatic patients with HOCM evaluated in Beijing Anzhen Hospital, Capital Medical University between March 2001 and December 2017, including 82 patients in the SM group and 102 patients in the medical group. Overall survival and HCM-related survival were mainly observed. Results The average follow-up time was 5.0 years. Compared to patients accepting medical therapy, patients treated with SM were associated with comparable overall survival (96.5% and 93.1% vs. 92.9% and 83.0% at 5 and 10 years, respectively; P=0.197) and HCM-related survival (98.7% and 98.7% vs. 94.2% and 86.1% at 5 and 10 years, respectively; P=0.063). However, compared to medical therapy, SM was superior at improvement of NYHA class (1.3±0.6 vs. 2.1±0.5, P<0.001) and mean reduction of resting left ventricular outflow (LVOT) gradient (78.5±18.6% vs. 28.3±18.4%, P<0.001). Multivariate analysis suggested that resting LVOT gradient in the last clinical examination was an independent predictor of all-cause mortality (HR=1.017, 95%CI: 1.000-1.034, P=0.045) and HCM-related mortality (HR=1.024, 95%CI: 1.005-1.043, P=0.012) in the entire cohort. Conclusion Compared with medical therapy, SM had comparable overall survival and HCM-related survival in mildly symptomatic HOCM patients, but SM had advantages on improving clinical symptoms and reducing resting LVOT gradient. Resting LVOT gradient in the last clinical examination was an independent predictor of all-cause mortality and HCM-related mortality.